Targeting neutrophil extracellular traps in severe acute pancreatitis treatment. (November 2020) - Hu, Jing; Kang, Hongxin; Chen, Huan; Yao, Jiaqi; Yi, Xiaolin; Tang, Wenfu; Wan, Meihua
Severe acute pancreatitis (SAP) is a critical abdominal disease associated with high death rates. A systemic inflammatory response promotes disease progression, resulting in multiple organ dysfunction. The functions of neutrophils in the pathology of SAP have been presumed traditionally to be activation of chemokine and cytokine cascades accompanying the inflammatory process. Recently, since their discovery, a new type of antimicrobial mechanism, neutrophil extracellular traps (NETs), and their role in SAP, has attracted widespread attention from the scientific community. Significantly different from phagocytosis and degranulation, NETs kill extracellular microorganisms by releasing DNA fibers decorated with granular proteins. In addition to their strong antimicrobial functions, NETs participate in the pathophysiological process of many noninfectious diseases. In SAP, NETs injure normal tissues under inflammatory stress, which is associated with the activation of inflammatory cells, to cause an inflammatory cascade, and SAP products also trigger NET formation. Thus, due to the interaction between NET generation and SAP, a treatment targeting NETs might become a key point in SAP therapy. In this review, we summarize the mechanism of NETs in protecting the host from pathogen invasion, the stimulus that triggers NET formation, organ injury associated with SAP involving NETs, methods to interrupt the harmful effects of NETs, and different therapeutic strategies to preserve the organ function of patients with SAP by targeting NETs.